29.0k views
5 votes
For the equation y = -2x + 1 A) complete the Table: X l Y -4 04B) Use the appropriate tool to graph the given equation

For the equation y = -2x + 1 A) complete the Table: X l Y -4 04B) Use the appropriate-example-1

1 Answer

6 votes

ANSWER:

a)

b)

Step-by-step explanation:

Given:


y=-2x+1

a) When x = -4, let's go ahead and solve for y;


\begin{gathered} y=-2(-4)+1 \\ y=8+1 \\ y=9 \end{gathered}

When x = 0, let's go ahead and solve for y;


\begin{gathered} y=-2(0)+1 \\ y=0+1 \\ y=1 \end{gathered}

When x = 4, let's go ahead and solve for y;


\begin{gathered} y=-2(4)+1 \\ y=-8+1 \\ y=-7 \end{gathered}

b) Using the above values, we can go ahead and the equation as seen below;

For the equation y = -2x + 1 A) complete the Table: X l Y -4 04B) Use the appropriate-example-1
For the equation y = -2x + 1 A) complete the Table: X l Y -4 04B) Use the appropriate-example-2
For the equation y = -2x + 1 A) complete the Table: X l Y -4 04B) Use the appropriate-example-3
For the equation y = -2x + 1 A) complete the Table: X l Y -4 04B) Use the appropriate-example-4
User KevinDTimm
by
4.7k points